Development of E-Worksheet with the TPACK Approach to Train Students' Digital Literacy and Higher Order Thinking Skills - Putri Ulyatun Niswah; Novi Ratna Dewi (Jurnal Penelitian Pendidikan IPA, 2024)
21st century skills that must be mastered by students in an era of rapid technological development, one of which is digital literacy and HOTS. Therefore, there is a need for innovation in form of E-worksheet with the TPACK approach to train students' digital literacy and HOTS. TPACK can integrate technology with learning. This study aims to analyze the validity of E-worksheets with the TPACK approach to train students' digital literacy and HOTS, and also to analyzing students' digital literacy and HOTS profiles after using the product. This type of research is Development which uses the ADDIE model. The average value of Aiken's E-worksheet products with the TPACK approach which was validated by 5 experts was 0.94 indicating that E-worksheet products developed were valid to be used to train students' digital literacy and HOTS. The digital literacy profile of 27 students is 7% very good criteria, 48% good criteria, and 45% good enough criteria. The HOTS profile of 27 students is 67% good criteria and 33% good enough criteria. It can be concluded that the E-worksheets with the TPACK approach is valid and can be used to train students' HOTS digital literacy.